Influence of Self-Efficacy and Perceived Valuableness in Research on the Research Engagement Among Librarians with Master’s Degree - Liezl L. Cadiog (Randwick International of Education and Linguistics Science Journal, 2024)
The study determined the influence of self-efficacy and perceived valuableness in research on the research engagement among librarians with Master’s Degree. A mixed-method research design was used. The instruments used in the study were adapted from Büyükoztürk, Brennan et al, and Serna. Participants consisted of 64 MLIS graduates from the Northern Mindanao and Caraga Region. Descriptive statistics and regression analysis were used to organize the data. Findings revealed that their efficacy in research was high; their perception of the valuableness of research was also high. Moreover, they were highly engaged in research behaviorally. Self-efficacy and their perception of the valuableness of research significantly influenced their behavioral research engagement. They admitted that their difficulties in research were related to data analysis and interpretation, review of related literature, introduction, conceptualization, theoretical framework, and research methods. In conclusion, self-efficacy and perceived valuableness in research in relation to research engagement will remain vital in today's librarianship due to the increased demand for services, developments, innovations, and technological advances.